Selected Chapters of Bayan Wujub Al-Hijra `ala’l-`Ibad of Shaykh Uthman Bn Fuduye, its Impact and Teachings to the Lives of Contemporary Muslim Ummah - Muhammad Maga Sule; Muhammad Maishanu Aliyu (Bulletin of Islamic Research, 2025)
This study examines selected chapters of Bayan Wujub Al-Hijra `ala’l-`Ibad of Shaykh Uthman Bn Fuduye and its teachings to the contemporary Muslim Ummah. The book articulates important religious and social principles on the necessity of Hijra (migration) in the pursuit of an equitable Islamic society. This study summarizes some important chapters in the book, describing their teachings and relevance to the contemporary Muslim Ummah. Through a critical reading of Shaykh Uthman Bn Fuduye discussions in Bayan Wujub Al-Hijra particularly the last five chapters, this study examines how the concept of Hijra its history and spiritual relevance in the life of the Ummah as it rejuvenate social justice and communal integrity during modern times. It also examines the applicability of these teachings to modern challenges that face Muslim societies, including matters of identity, migration, and socio-political engagement. By situating Shaykh Uthman Bn Fuduye discourses in the present socio-political realities, this paper demonstrates the enduring currency of his call for social reform and the creation of a unified Muslim identity. The study shows that Bayan Wujub Al-Hijra can yield timely lessons for Muslims today who want to address the issues of modernity without betraying their religious creed. Finally, this study seeks to enhance a greater understanding of the interplays among classical Islamic thought and contemporary realities to encourage the revival of the spiritual and communal traits reflected in Shaykh Uthman Ibn Fuduye's work.